Thermogravimetric analysis (TGA) for characterization of self-cementationof recycled concrete aggregates in pavement - Wang, Chong; Chazallon, Cyrille; Braymand, Sandrine; Hornych, Pierre (Thermochimica Acta, 2024)
International audience A key question concerning the application of recycled concrete aggregates (RCA) into pavement is the assessmentof self-cementing properties of RCA, which increase the strength and stiffness of unbound base and subbaselayers. In this paper, the assessment of self-cementing properties of RCA, the hydration of unhydrated binder andtheir influence on the microstructure and mechanical behaviour were studied by subjecting two different RCA(NRCA and ORCA, showing significantly different self-cementing properties), after curing for 0, 360 and 720days, to the thermogravimetric analysis (TGA), scanning electron microscopic analysis (SEM) and monotonictriaxial tests. The results show that the unhydrated binder content of NRCA is low (between 6.2% and 7.9% infines), and most of the unhydrated binder was hydrated after curing for 360 days. Besides, the sulfate attackproducts, ettringite, were also observed from both TGA and SEM, which could also lead to the self-cementingproperties. The hydration products of unhydrated cement and sulfate attack products not only form bonds betweenparticles, but also fill the small pores (width less than 3 μm), turning the open type of an unboundstructure to a rigid dense skeleton structure.